PELATIHAN PENDIDIKAN MULTIKULTURAL SEBAGAI UPAYA PENGUATAN HARMONI KEBERAGAMAN DI PERGURUAN TINGGI AGAMA - Abidin, Zaenal; Adibah, Ida Zahara; Ramidi, Ramidi (Jurnal Indonesia Mengabdi, 2024)
The dynamics of religious higher education institutions are closely related to the diversity of students’ social, cultural, and religious backgrounds. While diversity can serve as an integrative strength, it may also lead to tension if not properly managed. This community engagement program aimed to strengthen harmony in diversity through a participatory and contextual multicultural education training. The method consisted of a preparation stage through needs assessment, implementation of training activities in the form of interactive seminars, group workshops, cross-perspective dialogue simulations, and guided reflection, followed by evaluation using pre-tests, post-tests, and participatory observation. The results indicated an increase in participants’ understanding of multicultural education concepts, improved attitudes of tolerance and openness, and enhanced intercultural communication skills. Furthermore, the establishment of a student community concerned with diversity served as an indicator of program sustainability. Therefore, multicultural education training proved effective in strengthening harmony within religious higher education institutions and has the potential to be replicated in similar contexts.